Charity and stamps in Huelva during the Spanish Civil War. Part II - José Luis Guerra González (Universidad de Alicante, 2012)
This work continues the course of investigation started years ago with Postal History and stamps being considered a rich and interesting source for the study of the configuration of Nursing History. Given the fact that there are few studies at a national level, it is necessary to identify, describe and contextualise care and nursing phenomena in philatelic issues, in this case charity ones. From the study of these local charity-aimed stamps issued during the Spanish Civil War, using qualitative research techniques -particularly document observation in Huelva local archives, we verified that 34 towns in Huelva issued charity stamps during this period, with 95 varieties (coats of arms, monuments, motherhood, etc.). Of the 17 towns studied in the current Part II, there is no documental proof of connection between the stamps issue and the use of money collected for charities, whilst in Part I connection was found for 5 towns (Ayamonte, Cartaya, Cortegana, Isla Cristina and Trigueros). These "charity stamps" contributed to finance and manteinance of dining places and other charities, where poor people, women or children in need and prisoners were given food, clothing and sheltering.